Synthesis, characterization, and photocatalytic activity of ZnO nanostructures (Research, Society and Development, 2022)
This study investigated the synthesis, characterization of ZnO nanostructures using different precipitating agents in the photodegradation of rhodamine B (Rh B) using scanning electron microscopy (SEM), X-ray diffraction (XRD), fourier transform infrared (FTIR) and UV/Vis spectroscopy and zeta potential measurements. The results indicated the dependence of morphology on calcination temperature and the precipitating agent. The colloidal stability of these nanomaterials is affected with the morphology changed. The photocatalytic results showed that ZnO nanostructures synthesized with NH4OH (98.98%) were more efficient in the degradation of Rh B than ZnO nanostructures synthesized with NaOH (62.68%). This is related to ZnO (NH4OH) nanoparticles should present a higher density of electronic defects than ZnO (NaOH), producing energy levels between the band gaps. These results are potentially associated with a combination of optical and geometric factors that create other paths for the generation of electron-hole pairs in the precipitated ZnO nanocatalyst with different alkaline solutions.